PENGELOLAAN SAMPAH ORGANIK RUMAH TANGGA MENGGUNAKAN LOSIDA (LODONG SISA DAPUR) DI DUSUN DRONO SLEMAN DAERAH ISTIMEWA YOGYAKARTA - Euis Eka Pramiarsih; Anisa Febriana; Riska Windu Antika; Isnaini Khusnul Khotimah; Daffa Nur Ahmad; Sigid Sudaryanto (JURNAL PENGABDIAN MANDIRI, 2023)
Indonesia is a country with the fourth largest population in the world which certainly has an impact on waste production which increases every year. One of the organic waste produced is household waste. Improper waste management will certainly cause many serious disturbances. Based on the results of interviews and observations that have been made, waste management in Drono Hamlet, Tridadi Village is still not optimal, including burning waste, and collecting waste and then taking it by third parties. Therefore, the purpose of this community service is to provide counseling and utilization in managing organic waste through the activity of making lotions. The methods used in this activity were lectures, demonstrations and the practice of installing lotions by resource persons. The socialization process of kitchen waste management using lotions is carried out in three stages, namely the preparation stage, the socialization stage and the installation practice stage. From the results of the socialization and training that has been carried out for PKK women and several community leaders in Dusun Drono, Sleman, Sleman, DIY they have understood well how to use household organic waste for the future and this activity aims to provide independence in managing waste starting from from the source.